The Effect of Problem-based Learning Model Modified by Cognitive Load Theory on Mathematical Problem Solving Skills - Maulida Nur Zahara; Aan Hendrayana; Aan Subhan Pamungkas (Hipotenusa : Journal of Mathematical Society, 2020)
The background of the research is based on the fact that problem solving skills and its process is still low so that those create overload information. Another way to overcome this problem is to use a problem-based learning model which concerns on cognitive load theory. This study is aimed to determine on how students' problem solving skills when using a problem-based learning model modified by cognitive load theory. This research method uses a combination of research methods, namely quantitative as primary data and qualitative as secondary data. The population in this study are all students of grade VII Junior High School accredited A in Tangerang Regency. The sampling technique used is cluster random sampling and the selected sample is 60 students of Grade VII SMP Negeri 3 Cikupa which divided into experimental class and control class. The instruments in this research are 5 short essay tests and non-tests, questionnaire and interview. Based on data analysis’ result, it can be concluded that the achievement and improvement of students' mathematical problem solving abilities which use problem-based learning model modified by cognitive load theory is better than for those using problem-based learning generally.